PACIENTE SIMULADO VERSUS SIMULADOR DE ALTA FIDELIDADE: SATISFAÇÃO, AUTOCONFIANÇA E CONHECIMENTO ENTRE ESTUDANTES DE ENFERMAGEM NO BRASIL - Elaine Cristina Negri Santos; Rodrigo Guimarães dos Santos Almeida; Mateus Henrique Gonçalves Meska; Alessandra Mazzo (Universidade Federal do Paraná, 2021)
Objective: to assess and compare satisfaction, self-confidence and knowledge among Nursing students in the use of simulated patients and high-fidelity simulators. Method: a quasi-experimental study conducted in 2017 with 150 students from a private university The participants answered a pretest to assess knowledge and participated in a lecture and in skills training. After the simulation, the students answered the Satisfaction with Simulated Clinical Experiences scale and the Satisfaction and Self-confidence in Learning and Knowledge scale. The data were analyzed based on non-parametric tests. Results: the students showed high rates of satisfaction (93.5 and 92.5), self-confidence (4.3 and 4.4) and knowledge gain (6.2 and 6.4). There were no significant differences in the comparison between the simulated patient group and the high-fidelity simulator group regarding satisfaction, self-confidence and knowledge. Conclusion: the findings showed that well-prepared settings can be obtained with lower costs, and with an effective impact on the students' learning.